Effect of titanium ion implantation and deposition on hydrogenation behavior of Zr-1Nb alloy; Surface and Coatings Technology; Vol. 308 - Kashkarov E. B. Egor Borisovich; Nikitenkov N. N. Nikolai Nikolaevich; Sutygina A. N. Alina Nikolaevna; Syrtanov M. S. Maksim Sergeevich; Vilkhivskaya O. V.; Pryamushko T. S. Tatiana Sergeevna; Kudiyarov V. N. Victor Nikolaevich; Volesky L. (2016, 2016)
Title screen